Sustainability indicators using multaivariate analysis for irrigation low area of Acaraú Valley, Ceará - Lopes, Fernando (2009)
This study was carried out to develop an integrated analysis of sustainability determinant factors in the Perímetro Irrigado Baixo Acaraú (PIBAU), Ceará, Brazil. This study was performed by Factor Analysis/Principal Component Analysis (FA/PCA). The approach was developed at two different times: In September/2006, 22 cross-over forms were applied to small farmers; and in July/2007, when the evaluation of farmers’ irrigation systems were performed. The FA/PCA use allowed the identification of the best fit model to explain the sustainability of DIBAU. Five components were identified as responsible for the data structure, explaining 79.14% of the total variance, dissolved previously in 12 dimensions. The first factor (20.77 of variance) pointed to the acknowledgment and the use of agricultural production techniques. The second and the third factors represented a health and environmental group. The last two factors explained 26, 19% of the total variance assigned as irrigation efficiency and environmental education, respectively. Factor analysis reduced the number of variables, since the model best fitted occurred with 12 of the 27 analyzed variables.